2002
DOI: 10.1046/j.1365-2958.2003.03290.x
|View full text |Cite
|
Sign up to set email alerts
|

CesT is a bivalent enteropathogenicEscherichia colichaperone required for translocation of both Tir and Map

Abstract: SummaryMap is an enteropathogenic Escherichia coli (EPEC) protein that is translocated into eukaryotic cells by a type III secretion system. Although not required for the induction of attaching and effacing (A/E) lesion formation characteristic of EPEC infection, translocated Map is suggested to disrupt mitochondrial membrane potential, which may impact upon subsequent functions of the organelle such as control of cell death. Before secretion, many effector proteins are maintained in the bacterial cytosol by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…1). Indeed, it has been reported that the CesT-interacting type III effector Map is expressed at very low levels within EPEC (32), which may explain why it was not detected in our analyses. Nonetheless, from our observations and those from other reports (32-34), CesT physically interacts or is involved in the secretion of every LEE-encoded effector described to date, further strengthening its central role in EPEC pathogenesis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…1). Indeed, it has been reported that the CesT-interacting type III effector Map is expressed at very low levels within EPEC (32), which may explain why it was not detected in our analyses. Nonetheless, from our observations and those from other reports (32-34), CesT physically interacts or is involved in the secretion of every LEE-encoded effector described to date, further strengthening its central role in EPEC pathogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…30 -34). Recently, we demonstrated that the efficient secretion of many other EPEC type III effector proteins also required CesT (32,33), suggesting a possible interaction of these proteins with CesT. To identify new CesT interacting type III effector proteins, we took advantage of a ⌬sepD strain of EPEC that is known to hypersecrete type III effector proteins but not translocator proteins (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The chaperone CesT binds and enhances the translocation of Tir, Map and other LEE-effectors (EspH, EspJ, EspZ) and non-LEE (Nle) effectors (A, B1, B2, C, G, H1 and H2). 7,42 With the aim of analyzing the levels of Map, another CesT-dependent effector, we infected Nck-deficient cells with EPEC which carried a plasmid expressing Map fused in frame, to enable WB detection, with haemagglutinin (HA) and T7 epitope tags (WTCT7-map-HA).…”
Section: Phosphorylation Status Of Tir and Levels Of Tir Phosphorylatmentioning
confidence: 99%
“…The cesT gene encodes a multicargo type III secretion chaperone protein. CesT was initially discovered to be the chaperone for E. coli secreted protein Tir (Abe et al, 1999;Elliott et al, 1999), although subsequent studies implicated CesT roles for other type III effectors that are encoded within and outside of the LEE (Creasey et al, 2003;Thomas et al, 2005). LEE5 gene regulation is multifaceted, with at least two known promoter elements (Sánchez-SanMartín et al, 2001).…”
Section: Introductionmentioning
confidence: 99%